Peranan Tenaga Kerja Wanita Yang Bekerja Di Arab Saudi dalam Peningkatan Ekonomi Keluarga - Sihite, Dermawati (Muadalah, 2015)
The difficulty of finding a job with the level of education and low skills has its own problem in the society. It had an impact on changing the role of women. Not only required to perform internal functions as a wife, but also required to earn a living to support the family as a function of the external economy. One of the efforts that became Labor Women (TKW) as domestic workers in Saudi Arabia, because the income earned from the same job in the country is bigger. In addition they can also be all the pilgrimage (Haji), which will raise their social status in the community when they return to their homeland. This Study combine both qualitative and quantitative method. Results of this study indicatethat the use of their incomes as domestic workers in Saudi Arabia is 25% of the money they spend on the cost of daily living, 18% for renovating the house, 17% to pay off debt, 15% separately childrens school fees and his brother, 14 % for new businesses, and 11% is used to provide working capital loans to families. From this it can be seen that the presence of women who work as migrant workers contribute not only to his family but also to the siblings and other family aggota. In addition they are also able to address problems of families faced before leaving, which is to fulfill the needs of daily life arevery high, it is also a matter of debt that are not able to be paid by the family, and even some of them are capable of air over the business of the original only become laborers farmer and jobs that do not generate large revenues into efforts were quite promising